2007
DOI: 10.1002/elps.200700075
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of the complex dendrimeric contrast agent Gadomer using a combined approach of CE, MS, and CE‐MS

Abstract: The complex dendrimeric contrast agent Gadomer has been comprehensively characterized using various mass spectrometric techniques in combination with capillary electrophoresis. The analytical challenges arising from the structure of this analyte, e.g., the presence of a complex isotopic pattern originating from multiple gadolinium chelates could be overcome using this combined approach. Results obtained from initial MALDI-TOF-MS measurements could subsequently be complemented and confirmed by CE-ESI-TOF-MS mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Therapeutic and experimental drugs 14 , dyes 5, 6 , solubilizing chains 7 or a mixture of all three 8 can subsequently be added to these functional groups creating powerful multi-functional biological agents. There exist a large number of scientific reports regarding the therapeutic potential of dendrimers and especially polyamidoamino (PAMAM) dendrimers 912 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic and experimental drugs 14 , dyes 5, 6 , solubilizing chains 7 or a mixture of all three 8 can subsequently be added to these functional groups creating powerful multi-functional biological agents. There exist a large number of scientific reports regarding the therapeutic potential of dendrimers and especially polyamidoamino (PAMAM) dendrimers 912 .…”
Section: Introductionmentioning
confidence: 99%
“…Direct analysis of PAMAM dendrimers by MALDI 6, 1822 and ESI 2, 23 has also been reported. While these techniques are useful they are not sufficient for evaluating the purity, stability and detecting individual components of complex dendrimer mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Robust measurement of the purity of dendrimers is challenging . Mass spectrometric data are useful for showing the presence of impurities if a good method has been developed that shows a strong resolved molecular ion, but is not a good tool to accurately quantify impurities .…”
Section: Methodsmentioning
confidence: 99%
“…Another study is reported where CE-MS variants were used for the separation of gadomer, a dendrimeric contrast agent, from its related substances [207]. Initial mass measurements of low molecular weight IMPs were carried out using MALDI-TOF-MS, which were complimented and confirmed by CE-ESI-TOF-MS and CE-ESI-FT-ICR-MS.…”
Section: Ce-ms and Variantsmentioning
confidence: 99%